2018
DOI: 10.1111/cod.13169
|View full text |Cite|
|
Sign up to set email alerts
|

Contact sensitization to plants of the Compositae family: Data of the Information Network of Departments of Dermatology (IVDK) from 2007 to 2016

Abstract: Background The Compositae plant family includes many thousands of species, making it one of the most widespread group of plants worldwide. Sensitization to Compositae allergens may occur in private or in occupational settings. Objectives To monitor the current spectrum of sensitization to Compositae allergens, especially in cooks and florists. Methods We retrospectively analysed patch test results obtained with two Compositae mixes (CMs) (CM I and CM II; switch in October 2011), their individual components, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…in 29 Compositae‐sensitive patients showed that 90% of them reacted positively to PTH, 72% reacted positively to tansy, and 34% reacted positively to yarrow, whereas there were no positive reactions to Roman chamomile and arnica. Likewise, Bauer et al reported the highest prevalence of positive reactions to PTH and tansy, followed by yarrow, and a smaller number of positive reactions to German chamomile, Roman chamomile, and arnica in both 249 florists and >3000 controls.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…in 29 Compositae‐sensitive patients showed that 90% of them reacted positively to PTH, 72% reacted positively to tansy, and 34% reacted positively to yarrow, whereas there were no positive reactions to Roman chamomile and arnica. Likewise, Bauer et al reported the highest prevalence of positive reactions to PTH and tansy, followed by yarrow, and a smaller number of positive reactions to German chamomile, Roman chamomile, and arnica in both 249 florists and >3000 controls.…”
Section: Discussionsupporting
confidence: 70%
“…and the constituent test preparation are 1.2% and 1%, respectively. This may explain the difference in test results in Germany and Denmark, as well as the fact that only highly sensitive patients will react to the extract . In addition, the origin of the plant material may contribute: different chemotypes, that is, groups of plants belonging to the same species, but producing different sets of secondary metabolites because of genetic variability, of chamomile exist, and this is also true of tansy, yarrow, and arnica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the multitude of plant constituents beyond these patch test preparations, it is often necessary to test with extracts, the composition of which may vary with the season of harvest, geographic region, chemotype, that is, the (epi)genetically determined and varying spectrum of plant substances of plants belonging to one species on morphological grounds, and other factors, making standardisation difficult. A large multicentre study from the IVDK including 1492 cooks, 851 florists and 118,358 other occupations found an increased prevalence of positive reactions to Compositae mixes and the SL mix in florists, corresponding to their occupational exposure, and confirmed that additional testing of SL mix will yield a notable share of contact allergies not detected with Compositae mixes, namely, 89 patients positive solely to SL mix in addition to 533 patients (also) reacting to a Compositae mix [269]. A Danish investigation concluded that SL mix is an indispensable, although insufficient, screening mixture in that country which may be safely supplemented with Compositae mix 2.5% and parthenolide in the TRUE Test™ system for screening, but, when Compositae sensitization is suspected, further extracts should be tested on the basis of the history [270].…”
Section: Woods Plants and Plant-derived Materialsmentioning
confidence: 75%
“…In a German retrospective multicentre study on Compositae sensitization in cooks, florists, and a large control group, 24 no case of active sensitization to either CM 5% or CM II 5% was reported. However, in 15.5% of the patients, the application time was one day, and only D3/D4 readings were analyzed.…”
Section: Discussionmentioning
confidence: 97%